Aktualisasi Teori-Teori Pembelajaran dalam Pola Asuh di Era Digital - Mahdi, Mahdi; Zulfikar, Teuku; Shadiqin, Sehat Ihsan (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This research reveals the issue of actualizing learning theories in parenting in the digital era, using a research synthesis approach in exploring relevant theories and for the accuracy of the data collected, qualitative analysis was used. The results of this research; First, parents as educators and children as students are related by blood. Therefore, his authority is natural. So that in the process of interaction between parents and children is very close. Second, in behaviorism theory, parents act as teachers who provide stimulus, provide reinforcement, and manage the learning environment to achieve learning goals. In cognitivism theory, parents should offer activities that promote cognitive development, improve problem solving skills, and stimulate critical thinking. Meanwhile, in constructivism theory, parents must learn strategies for creating a learning environment for children, in order to foster curiosity, provide hands-on practical experience, and encourage collaboration. Third, challenges in raising children in the digital era, including; digital distraction, overstimulation, and balancing screen time.